1998
DOI: 10.1176/jnp.10.2.224
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of d-Cycloserine Treatment in Alzheimer's Disease

Abstract: D-cycloserine is a partial agonist on the glycine site of the N-methyl-D-aspartate glutamate receptor. This double-blind crossover study of 15 mg D-cycloserine in Alzheimer's disease patients did not demonstrate clinical benefit. Higher medication dosage or long-term treatment may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Therefore, studies were recently conducted to explore if the administration of CYC could improve cognitive functions in humans. Indeed, in some studies, it has been shown to improve cognitive functions in Alzheimer and schizophrenic patients, if administered in a proper dosage (Goff et al, 1995(Goff et al, , 1999Tsai et al, 1998Tsai et al, , 1999, although the results achieved so far are mixed (Laake and Oeksengaard, 2002). Whether the improvement of cognitive functions is caused by an enhancement of NMDA receptor efficacy has so far not been tested in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies were recently conducted to explore if the administration of CYC could improve cognitive functions in humans. Indeed, in some studies, it has been shown to improve cognitive functions in Alzheimer and schizophrenic patients, if administered in a proper dosage (Goff et al, 1995(Goff et al, , 1999Tsai et al, 1998Tsai et al, , 1999, although the results achieved so far are mixed (Laake and Oeksengaard, 2002). Whether the improvement of cognitive functions is caused by an enhancement of NMDA receptor efficacy has so far not been tested in humans.…”
Section: Introductionmentioning
confidence: 99%
“…It is classified as a second line drug for the treatment of tuberculosis. It is able to penetrate the central nervous system (CNS) thus its use in Alzheimer's disease and schizophrenia (Goff, Henderson, Evins, & Amico, 1999;Goff, Tsai, Manoach, & Coyle, 1995;Tsai, Falk, & Gunther, 1998;Tsai, Falk, Gunther, & Coyle, 1999) while the effect it has on anxiety disorders remains unclear (Ori et al, 2015;Schade & Paulus, 2016). D-Cycloserine inhibits cell wall synthesis in Gram positive bacteria and M.tuberculosis by inhibition of the incorporation of D-alanine into peptidoglycan pentapeptide (Lambert & Neuhaus, 1972;Vyshepan, Ivanova, & Ledneva, 1962;Wargel, Shadur, & Neuhaus, 1971).…”
Section: D-cycloserine (D-4-amino-3-isoxazolidone) Has Better Activitmentioning
confidence: 99%
“…Supporting neurotrophic/cognitive effects, DCS can improve cognitive functions in animal studies [171,172] and is used clinically in conjunction with CBT interventions [127]. However, cognition-enhancing effects of DCS in AD have not been conclusively demonstrated [173][174][175].…”
Section: Cognitive Impairment and Dementiamentioning
confidence: 99%